2014
DOI: 10.1002/ange.201308920
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Hybrid‐Gated Multifunctional Mesoporous Silica Nanocarriers for Dual‐Targeted and MicroRNA‐Responsive Controlled Drug Delivery

Abstract: The design of an ideal drug delivery system with targeted recognition and zero premature release, especially controlled and specific release that is triggered by an exclusive endogenous stimulus, is a great challenge. A traceable and aptamer-targeted drug nanocarrier has now been developed; the nanocarrier was obtained by capping mesoporous silicacoated quantum dots with a programmable DNA hybrid, and the drug release was controlled by microRNA. Once the nanocarriers had been delivered into HeLa cells by aptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…Enzyme‐induced hydrolysis of the pore‐capping saccharides could be used to open the closed pores, and the design was validated by the intracellular drug release experiments. Zhang et al reported DNA‐capped MSNs that can release the loaded drugs upon hybridization with complementary base pairs . By designing the DNA stand to hybridize exclusively with an oncogenic microRNA, a combination of chemotherapy and gene therapy could be possible.…”
Section: Structures Of Multifunctional Np Platformsmentioning
confidence: 99%
“…Enzyme‐induced hydrolysis of the pore‐capping saccharides could be used to open the closed pores, and the design was validated by the intracellular drug release experiments. Zhang et al reported DNA‐capped MSNs that can release the loaded drugs upon hybridization with complementary base pairs . By designing the DNA stand to hybridize exclusively with an oncogenic microRNA, a combination of chemotherapy and gene therapy could be possible.…”
Section: Structures Of Multifunctional Np Platformsmentioning
confidence: 99%
“…The classical drug transfer system skeleton is to integrate a molecular navigator with “weapon” drug molecules. The design of an ideal drug delivery system with targeted recognition, zero premature, and spatial–temporal controlled release remains great challenges in biomedicine . The DNA aptamers are short single‐stranded oligonucleotides that are biocompatible, stable, and, importantly, they are able to specifically recognize and effectively bind to their targets …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…After internalization into specific tumor cell, aptamer AS1411 showed high binding affinity to nucleolin, resulting in the pore opening and drug releasing. Zhu and co‐workers reported a traceable and dual‐targeted drug delivery system based on DNA‐hybrid‐capped mesoporous silica‐coated quantum dots (Figure b) . Since microRNA‐21 (miR‐21) was overexpressed in the cytoplasm of various cancer cells, the delivery of antisense miR‐21 can be an efficient way to inhibit and further eradicate of tumor cells .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 When oligonucleotides are used as capping molecules for the fabrication of bio-gated delivery systems, the cargo release occurs in the presence of the complementary oligonucleotide or in the presence of deoxyribonucleases, or after heating (Figure 2b). [31][32][33][34][35] Another alternative chemical reaction for controlling release with capping materials is host-guest reorganization between α-cyclodextrin (α-CD) and anilinoalkane groups based on hydrogen-bonding. 36 Specifically, anilinoalkane groups were covalently bonded onto MSNs with a free anilino group on the end of the linker.…”
Section: Controlled Release Of Therapeutics From Siomentioning
confidence: 99%